2019
DOI: 10.3389/fphar.2019.00618
|View full text |Cite
|
Sign up to set email alerts
|

Bergenin Activates SIRT1 as a Novel Therapeutic Agent for Osteogenesis of Bone Mesenchymal Stem Cells

Abstract: Bone mesenchymal stem cells (BMSCs) are important candidates for bone regeneration. The role of Bergenin, a C-glucoside of 4-O-methyl gallic acid obtained from the species, Bergenia, in BMSC osteogenesis has not yet been elucidated. We therefore investigated the effects of Bergenin on the osteogenesis of BMSCs and found that Bergenin enhanced osteoblast-specific markers and downregulated the adipocyte-specific markers in vitro . Furthermore, using a rat calvarial defect model, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…Bergenin is the C-glucoside of 4- O -methyl gallic acid and can be found in several medicinal plants, including Bergenia crassifolia and Corylopsis spicata ( Liang et al, 2017 ). Bergenin has been reported to have multiple biological activities, including antiarthritic ( Jain et al, 2014 ; Singh et al, 2017 ), immunomodulatory ( Wang et al, 2017 ; Kumar et al, 2019 ), antidiabetic ( Veerapur et al, 2012 ), osteogenic ( Hou et al, 2019 ), neuroprotective ( Barai et al, 2019 ; Ji et al, 2019 ), and wound-healing effects ( Mukherjee et al, 2013 ). Wang et al (2017) showed that bergenin attenuated colitis by activating the peroxisome proliferator-activated receptor (PPAR) γ.…”
Section: Introductionmentioning
confidence: 99%
“…Bergenin is the C-glucoside of 4- O -methyl gallic acid and can be found in several medicinal plants, including Bergenia crassifolia and Corylopsis spicata ( Liang et al, 2017 ). Bergenin has been reported to have multiple biological activities, including antiarthritic ( Jain et al, 2014 ; Singh et al, 2017 ), immunomodulatory ( Wang et al, 2017 ; Kumar et al, 2019 ), antidiabetic ( Veerapur et al, 2012 ), osteogenic ( Hou et al, 2019 ), neuroprotective ( Barai et al, 2019 ; Ji et al, 2019 ), and wound-healing effects ( Mukherjee et al, 2013 ). Wang et al (2017) showed that bergenin attenuated colitis by activating the peroxisome proliferator-activated receptor (PPAR) γ.…”
Section: Introductionmentioning
confidence: 99%
“…mscMSCs, a resident cell population existing in the bone marrow, are involved in the catabolic-anabolic coupling of bone metabolism [ 7 , 23 ]. MSCs have multiple lineages of differentiation potential, including chondrogenesis, osteogenesis, adipogenesis, and stromal cells differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides both in vitro and in vivo evidence to show that SIRT1 expression is upregulated in damaged tubular cells during cisplatin-induced AKI. Previous studies have demonstrated the beneficial effects of SIRT1 in many organs, including the liver (Zhu et al, 2014;Abd Elwahab et al, 2017), heart (Li et al, 2019), bone (Hou et al, 2019), and FIGURE 7 | SIRT1 mediates the beneficial effects of FGF21 on cisplatin-induced mouse AKI. (A,B) Representative immunoblotting analysis of SIRT1 in SIRT1 knockdown mice.…”
Section: Discussionmentioning
confidence: 99%